Larval morphology of Lebertia longiseta Bader, 1955, L. dubia Thor, 1899 and Oxus nodigerus Koenike, 1898 (Acari, Hydrachnidia: Lebertiidae, Oxidae) - Tuzovskij, Petr V. (Zootaxa, 2013)
Illustrated descriptions of the larvae of the water mite species of Lebertia longiseta Bader, 1955, Oxus nodigerus Koenike, 1898 and redescription of the larva L. dubia (Thor, 1899) are presented.